Living with rheumatoid arthritis - Shlotzhauer, Tammi L. (Johns Hopkins University Press, 2003)
Annotation A trusted guide and an invaluable resource, Living with Rheumatoid Arthritis offers practical advice for the millions of people coping with this painful disease. Now thoroughly revised and expanded, in a second edition, this book brings readers up to date with the latest methods of diagnosis and treatment. Building on their accessible explanation of the disease and its causes, the authors describe the essential components of care: medication, joint protection, physical activity, and good nutrition. They provide a wealth of new information on medications, including biologic response-modifiers, alternative and complementary approaches, and treatments for osteoporosis (which often accompanies rheumatoid arthritis), and they describe safe and effective ways to cope with pain, stiffness, and fatigue. The book helps readers understand their own emotional responses, as well as those of family and friends, and, because the disease often entails lifestyle changes, it provides practical advice for achieving as normal a life as possible. With the latest information on medication, nutrition, and resources (online and off), this volume is a complete and comprehensive guide to the management of a difficult disease.